Paraffin wax deposition and its remediation methods on crude oil pipelines: A systematic review - Basem Elarbe,; Ibrahim Elganidi,; Norida Ridzuan,; Norhayati Abdullah,; Kamal Yusoh, (Maejo International Journal of Energy and Environmental Communication, 2021)
Due to low-temperature circumstances, precipitation and paraffin wax deposition in manufacturing pipes and transportation tubes from offshore to onshore are significant challenges in the oil and gas sector. It may cause a reduction in output, a shutdown, pipeline blockage, and increased fluid viscosity. The most often used method for resolving this problem is to inject a wax inhibitor into the channel. Most current studies about paraffin wax are disseminated in literary works or exist as tacit knowledge in professional crania. This review research aims to exchange information and fulfil the deficits caused by providing a complete overview of the chemistry of paraffin wax precipitation and accumulation and causes, processes, and detection. It also discusses the overall impacts of paraffin wax deposition, how to deal with it, and several cleaning options. It also includes a conclusion and beneficial tips.